Fluid and crystallized abilities as predictors of everyday cognitive competence in middle-aged adults - Juras, Luka (Psihološka obzorja (Ljubljana), 2024)
The competence to independently solve everyday tasks is crucial for prosperous aging. Less is known about the contribution of fluid abilities and crystallized abilities to everyday cognitive competence in middle-aged adults. The current preliminary study examines the relative contributions of fluid intelligence and crystallized ability to everyday cognitive competence in a sample of 59 middle-aged adults (age range 49–65 years). Fluid intelligence and crystallized ability had statistically significant bivariate correlations with the everyday cognitive competence in our sample. Surprisingly, neither of two cognitive predictors had an independent contribution in predicting everyday cognitive competence when simultaneously introduced in hierarchical regression analysis. Our preliminary results call for future investigation of the complex relationship between various basic cognitive abilities and everyday cognitive competence.
Keywords: cognitive ability; Everyday problems test; fluid intelligence; fluidna inteligentnost; kognitivne sposobnosti; middle adulthood; srednja odraslost; Test vsakodnevnih problemov